2021
DOI: 10.3390/pharmaceutics13081191
|View full text |Cite
|
Sign up to set email alerts
|

External Evaluation of Population Pharmacokinetic Models and Bayes-Based Dosing of Infliximab

Abstract: Despite the well-demonstrated efficacy of infliximab in inflammatory diseases, treatment failure remains frequent. Dose adjustment using Bayesian methods has shown in silico its interest in achieving target plasma concentrations. However, most of the published models have not been fully validated in accordance with the recommendations. This study aimed to submit these models to an external evaluation and verify their predictive capabilities. Eight models were selected for external evaluation, carried out on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The predictive performance of infliximab PopPK models was previously externally evaluated in patients with inflammatory diseases, 30 including patients with IBD. 31,32 In the studies of Santacana et al 31 and Schräpel et al, 32 the two models developed by Fasanmade et al 33,34 (using data from the phase III trials) demonstrated the best predictive…”
Section: Discussionmentioning
confidence: 99%
“…The predictive performance of infliximab PopPK models was previously externally evaluated in patients with inflammatory diseases, 30 including patients with IBD. 31,32 In the studies of Santacana et al 31 and Schräpel et al, 32 the two models developed by Fasanmade et al 33,34 (using data from the phase III trials) demonstrated the best predictive…”
Section: Discussionmentioning
confidence: 99%
“…To improve the initiation of fluoropyrimidines treatment in DPD deficient patients, pharmacokinetics Bayesian tools could be used [ 41 , 42 , 43 ]. It is well known that plasma concentrations of 5-FU and capecitabine are associated with both side effects and responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, Model-Informed Precision Dosing (MIPD) is a more precise alternative, based on the use of population pharmacokinetics (PopPK) models and a prospective Bayesian approach to increase the homogeneity in the drug exposure in patients and, therefore, to improve outcomes of treatments [ 61 ]. Some authors have carried out MIPD of adalimumab and infliximab in IBD patients, applying PopPk models found in the literature [ 62 , 63 ]. However, further investigations in this line are required to estimate its cost and compare it with the ones obtained from a TDM strategy.…”
Section: Discussionmentioning
confidence: 99%